Perancangan UI/UX aplikasi berbasis mobile Menggunakan Metode Design Thinking study khasus SISFO SKPI UNIMMA - Alvine Candra; Pristi Sukmasetya; Purwono Hendradi (TeIKa, 2023)
The development of mobile technology and the use of mobile applications are increasing, especially in the campus environment. The Information System for Certification of Graduation Supporting Documents (SISFO SKPI) UNIMMA is a system that functions as a storage and data processing place to help the process of issuing certification of graduation supporting documents for students. Currently, UNIMMA still uses a website-based application. However, the use of the SISFO SKPI UNIMMA website is not optimal and does not pay attention to good User interface (UI) and User experience (UX) design, so users feel uncomfortable when using the application. Therefore, this study aims to redesign the User interface (UI) and User experience (UX) of the SISFO SKPI UNIMMA application from the website to a mobile-based application using the Design thinking method. The Design thinking method was chosen because it is able to explore various possible solutions by involving users as the main subject. This research was conducted with the Design thinking stages, namely empathize, define, ideate, prototype, and testing. The results of the study show that the UI/UX design of the SISFO SKPI UNIMMA application using the Design thinking method is able to improve the quality of the user experience in using the SISFO SKPI UNIMMA application. This is evidenced by the results of usability testing which show a significant increase in user satisfaction with the application. The UI/UX design of the SISFO SKPI UNIMMA application is expected to be a basis for further development of the SKPI UNIMMA application.